DETERMINANTS OF GREEN PURCHASE INTENTIONS-EMPIRICAL ANALYSIS WITH REFERENCE TO HYDERABADJNDIA - SravaniChari, Dr. V. (The journal of contemporary issues in business and government, 2022)
Increasing knowledge on various environmental problems among consumers has led them to move towards the path of sustainable consumption. As a result, attention towards the“ greenaspect” ofproducts,aswellastheireffectsonEarthhasgainedprominence. On the other hand concerntowardshealthisbecomingoneofthepriorconcernsofconsumers,makingthemadopta healthy lifestyle, which is being showcased in the form of purchasing and consuming greenproducts. The objective of this paper is to studythe individual’s attitude towards greenproducts, health consciousness andsocial influence on consumer green purchase intentions of organicfoodproductsamongtheconsumersofHyderabad.Thestudyisconductedbycollectingquestionnaires from the consumers visiting organic stores for buying organic food products.The samples collected were 200for conducting the data analysis. The statistical tools used inthe study are Correlation,Factor analysis, Multiple Linear Regression Analysis. Attitudetowards green products emerged as a predominant factor, positively influencing the purchaseintentions of individuals. The findingsdepicted that green market is in evolving stage indeveloping countries like India and opens an avenue for marketers to exploit the opportunities available ingreen marketindustry.